OVERVIEW OF URIC ACID LEVEL EXAMINATION RESULTS IN GREEN VEGETABLE CONSUMERS IN MOUTONG DISTRICT (Journal of Health, Technology and Science (JHTS), 2025)
Increased uric acid levels in the body occur due to several factors, one of which is consuming foods high in purines. To prevent this from happening, it is important t o pay attention to the frequency of consumption of foods containing purines, one of which is green vegetables. This study aims to examine uric acid levels in people who consume excessive amounts of green vegetables in Moutong District. The research method used a quantitative approach. The type of research design used was a descriptive design with an observational descriptive design. It used 30 samples of excessive green vegetable consumers in Moutong District. The results of this study obtained 30 samples, consisting of 19 females and 11 males. The results showed that the average uric acid levels were within the normal range. It can be concluded that excessive consumption of green vegetables can increase uric acid levels, but this can also be influenced by several other factors, such as genetic history, age, gender, alcohol consumption, and consumption of other foods high in purines.